Integrated traditional Chinese and western medicine nursing of a psoriasis patient with acute poisoning caused by oral methotrexate (1例银屑病患者口服甲氨蝶呤致急性中毒的中西医结合护理) - LI Ting (李婷); CHEN Yuefang (陈月芳); TANG Juping (汤菊萍) (中西医结合护理)
This paper summarizes the nursing experience of integrated traditional Chinese and Western medicine for a psoriasis patient with acute poisoning caused by oral methotrexate. Based on the comprehensive evaluation of skin lesion, a multidisciplinary team was established to implement the disease management program consisted of individualized nursing interventions on skin and mucosa, pain and nutrition status. In addition, Traditional Chinese Medicine five-tone music therapy and Tuina was carried out to improve the physical condition, skin wound healing and sleep quality of the patient. (本文总结1例银屑病患者口服甲氨蝶呤致急性中毒的中西医结合护理经验。基于患者皮损情况和护理评估, 多学科联合制定疾病管理方案, 对患者皮肤黏膜、疼痛、营养进行个性化护理干预, 并配合中医五音疗法和推拿技术, 改善患者机体状况, 促进皮肤黏膜愈合, 提高睡眠质量。)